HYDROGEOCHEMICAL EVOLUTION OF GROUNDWATER IN A MEDITERRANEAN COASTAL AQUIFER, MERSIN-ERDEMLI BASIN (TURKEY) - Demirel Z.; Güler C. (My University, 2006)
In this study, hydrogeologic and hydrochemical information from the Mersin-Erdemli groundwater system were integrated and used to determine the main factors and mechanisms controlling the chemistry of groundwaters in the area and anthropogenic factors presently affecting them. The PHREEQC geochemical modeling demonstrated that relatively few phases are required to derive water chemistry in the area. In a broad sense, the reactions responsible for the hydrochemical evolution in the area fall into four categories: (1) silicate weathering reactions; (2) dissolution of salts; (3) precipitation of calcite, amorphous silica and kaolinite; (4) ion exchange. As determined by multivariate statistical analysis, anthropogenic factors show seasonality in the area where most contaminated waters related to fertilizer and fungicide applications that occur during early summer season.
Keywords: COASTAL AQUIFER; WATER-ROCK INTERACTION; PRINCIPAL COMPONENTS ANALYSIS; CLUSTER ANALYSIS; MERSIN